Description of three new species of the genus Myxobolus infecting carp fishes of India - Ghosh, Subarna (J Parasit Dis, 2016)
Myxobolus Bütschli, 1882 (Myxozoa, Myxosporea, Bivalvulida, Myxobolidae) is an important parasitic protozoan of freshwater fishes reported from almost all over the world. The severity of infection may lead to mortality of the host fish. The present paper deals with the description of three new species of Myxobolus Bütschli, 1882, Myxobolus sonarpurensis sp. nov., Myxobolus elongatum sp. nov. and Myxobolus petalum sp. nov. from a freshwater minor carp Labeo bata (Hamilton, 1822) and major carp Labeo rohita (Hamilton, 1822) respectively from West Bengal, India. Spores of Myxobolus sonarpurensis sp. nov. measures 12.16 µm × 6.74 µm, with two elongated unequal sized polar capsules measuring, 8.84 µm × 3.019 µm and 7.71 µm × 3.12 µm. Spores of Myxobolus elongatum sp. nov. are 16.23 µm × 7.9 µm with two equal polar capsules 8.896 µm × 3.468 µm and 6.51 µm × 3.46 µm. In comparison to aforementioned two new species, Myxobolus petalum sp. nov. have two equal polar capsules, 7.905 µm × 2.975 µm (2.9 µm) in each spore, 12.07 µm × 5.95 µm.